Stratification of the risk of bipolar disorder recurrences in pregnancy and postpartum. (21st June 2018) - Di Florio, Arianna; Gordon-Smith, Katherine; Forty, Liz; Kosorok, Michael R.; Fraser, Christine; Perry, Amy; Bethell, Andrew; Craddock, Nick; Jones, Lisa; Jones, Ian
Abstract : Background: Pregnancy and childbirth are a period of high risk for women with bipolar disorder and involve difficult decisions particularly about continuing or stopping medications. Aims: To explore what clinical predictors may help to individualise the risk of perinatal recurrence in women with bipolar disorder. Method: Information was gathered retrospectively by semi-structured interview, questionnaires and case-note review from 887 women with bipolar disorder who have had children. Clinical predictors were selected using backwards stepwise logistic regression, conditional permutation random forests and reinforcement learning trees. Results: Previous perinatal history of affective psychosis or depression was the most significant predictor of a perinatal recurrence (odds ratio (OR) = 8.5, 95% CI 5.04–14.82 and OR = 3.6, 95% CI 2.55–5.07 respectively) but even parous women with bipolar disorder without a previous perinatal mood episode were at risk following a subsequent pregnancy, with 7% developing postpartum psychosis. Conclusions: Previous perinatal history of affective psychosis or depression is the most important predictor of perinatal recurrence in women with bipolar disorder and can be used to individualise risk assessments. Declaration of interest: None.